Intravenous calcium Gluconate alleviates Lead-induced abdominal pain, a randomized clinical trial - Masoud Mayel; Saleh Hamzeh; Salile Shahabi Rabori; Sareh Ghasemirad; Nasim Zamani; Hossein Hassanian-Moghaddam (BMC, 2020)
Abstract Background In 2016, in a lead poisoning outbreak in Iran, physicians reported thousands of opium users who presented to emergency departments (EDs) with intractable severe abdominal pain which did not respond to any narcotic medication. During the same period of time, we investigated the efficacy of intravenous calcium gluconate in alleviating lead-induced abdominal pain. Methods In a single-center, single blinded, randomized controlled trial, a convenient sample of adult opium-addicted patients who presented to an academic ED with abdominal pain and had an initial diagnosis of lead poisoning were included and randomly subjected to two treatment groups receiving conventional treatment (morphine 0.1 mg/kg + normal saline; group 1) and conventional treatment plus 1 g of intravenous calcium gluconate (group 2) to alleviate their abdominal pain. The visual analogue scale (VAS) was determined by each patient (0 to 100 mm) before treatment, and 15, 30, and 60 min after intervention. Results A total of 50 patients (25 in each group) were enrolled. Blood lead levels, VAS scores before treatment, and mean administered dose of morphine were similar between the two groups. After treatment, mean VAS score dropped to 64.7± 10.4 vs. 67.1± 10.9 at 15 min (P = 0.437), 64.6± 10.9 vs. 58.0 ± 11.2 at 30 min (P = 0.041), and 63.8± 10.7 vs. 53.6± 10.9 at 60 min (P = 0.002) in groups 1 and 2, respectively. Conclusion Intravenous calcium gluconate administration along with morphine can improve abdominal pain in lead poisoning due to the ingestion of lead-contaminated opium. Further interventional studies are recommended to see if response to calcium salts in suspected lead-induced abdominal pain can rule in lead toxicity. Trial registration IRCT20171009036661N2 . Registered 27 May 2018 - Retrospectively registered,